Accuracy of Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) Score System as An Early Diagnostic Predictor of Necrotizing Fasciitis in A Tertiary Referral Hospital in Bandung, Indonesia - Teguh Marfen Djajakusumah; Rani Septrina; Arief Dwinanda (Althea Medical Journal)
Background: Necrotizing fasciitis (NF) is a serious infection that can rapidly kill tissue and potentially lead to multiple organ failure. Early diagnosis and treatment are essential for survival. The laboratory risk indicator for necrotizing fasciitis (LRINEC) score may aid in early detection of NF. Although initially promising, studies on the effectiveness of LRINEC have shown mixed results. This study aimed to investigate the accuracy of LRINEC in predicting NF.